MORTALITY FROM RESPIRATORY SYSTEM CANCER IN THE TOMSK REGION - E. L. Choynzonov; L. D. Zhuikova; I. N. Odintsova (Сибирский онкологический журнал, 2018)
A retrospective epidemiological analysis of the mortality from respiratory system cancer among the population of the Tomsk region for a ten-year period was carried out using data drawn from  the official population and mortality statistics of the Tomsk region.  Cancer has the second leading cause of death behind cardiovascular disease. Respiratory system cancer is the 3-rd most  common cause of cancer-related death after cancers of the digestive system and genital organs. The standardized mortality  rate for respiratory system cancer among the rural population is significantly higher than that in the urban population (p<0.05). Over the study  period, the respiratory system mortality rate decreased for males  (р=0.0000) and remained relatively constant for females. The  lifetime risk of dying from respiratory system cancer in 2016 in the  Tomsk region was higher than the national average. For men, it was  the highest among the main localizations. Compared to 2007, the  mortality rate decreased, as the risk of lung cancer death in men  decreased. The lifetime risk of dying from respiratory system cancer  was higher in the rural population than in the urban population. The indicator of «severity» of the disease indicates an unfavorable  situation in terms of quality and completeness of statistical recording of patients and early diagnosis of respiratory cancer, especially in  urban areas of the Tomsk region. In order to ensure timely and  adequate routing of patients with suspected malignant neoplasm and  timely diagnosis, the continued implementation of the Population-based Cancer Registry with coverage of all administrative territories and areas is of great importance.